Identification and characterization of bacterial biofilm production in clinical isolates of Staphylococcus spp. against antimicrobials - Martins, Lamartine Rodrigues; Silva, Mariana Quitéria de Morais; Medeiros Neto, Carlos Alberto; Pimentel, Maria Izabelly Silva; Rocha, Igor Vasconcelos; Oliveira, Sibele Ribeiro de (Revista de Epidemiologia e Controle de Infecção, 2021)
Justification and Objectives: Circulating blood is sterile and the presence of microorganisms can be of clinical interest, especially in the hospital environment, being able to cause infectious processes and substantially increase morbidity and mortality. The objective of this work was to characterize the isolates of the genus Staphylococcus spp. from bloodstream infections as to the production of bacterial biofilm and resistance to the main antimicrobials used in clinical practice. Methods: Blood cultures were collected with an indication of positivity for bacterial growth from multiple sectors of the study hospital, which were subsequently processed to identify the bacterial genus through the use of phenotypic tests for Gram positive bacteria. The verification of the resistance profile was performed following the Kirby-Bauer disk diffusion. The identification of the production and quantification of the bacterial biofilm occurred following the protocol described by O’toole (2010). Results: The most frequent clinical isolate was Coagulase negative Staphylococci 38 (54.29%), followed by Staphylococcus aureus 32 (45.71%). Resistance to erythromycin, norfloxacin, levofloxacin and azithromycin was observed in most isolates (70%). Regarding methicillin, more MRSA (59.38%) than MR-CONS (47.37%) were isolated. The ICU was the place where the formation of the biofilm showed indicative data of greater adherence, which was associated with MRSA strains. Conclusion: The bacterial isolates associated with bloodstream infections showed high resistance to antimicrobials. The presence of MRSA and MR-CONS with strong and/or moderate biofilm production capacity represents a greater risk to the health of patients affected by infections caused by these agents.